Another Anglo-Indian Cuisine: The Cousins of Curry, Featuring ‘A Few Nice Pies’ - Perkins, Blake (Petits Propos Culinaires, 2015)
This article looks at some of the other hybrid dishes -- the cousins of curry -- represented in Anglo-Indian cooking and how they have been treated by cookbook authors, noting many neglected recipes.